The Role of Principal Leadership in Improving the Quality of Human Resources (HR) at the Development Madrasah Aliyah in South Tangerang City - Prayogo Pangestu; Hilmi Luthfiyah; Hasyim Asy’ari (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the role of principal leadership in improving the quality of Human Resources (HR) at the South Tangerang City Development Madrasah Aliyah. In the context of education, the quality of HR is one of the important factors that determine the success of an educational institution. The principal, as the main leader, plays a key role in guiding and managing HR to achieve optimal educational goals. This study uses a qualitative approach with a case study method, which involves in-depth interviews with the principal, teachers, and administrative staff at the madrasah. The results of the study indicate that the principal plays a role in several important aspects, including planning and implementing teacher professional development programs, improving the quality of teaching through training, and managing resources to create a conducive work environment. In addition, the principal also plays a role in motivating and providing moral support to teachers to continue to develop and improve their competence. Other factors that also play an influence are clear policies, effective communication, and the principal's ability to manage change. Thus, the role of the principal's leadership greatly influences the improvement of HR quality at the South Tangerang City Development Madrasah Aliyah, which in turn will improve the quality of education at the madrasah.